Assessing Interactive Videodisc in Extension - S. Kay Rockwell; Thomas G . Tate; James W. King (Journal of Applied Communications, 1989)
If Extension is going to use interactive videodisc as a program delivery method in the future, the technology must be explored and systematically evaluated in a variety of learning situations. Studying the adoption of the technology in Extension challenges us to (a) identify those interested in exploring the medium, (b) develop an overall strategy for testing the technology, and (e) organize a method for delivering the evaluative information to decision makers. This article poses a considerable number of questions to be addressed as interactive videodisc is tested for its application in transferring information in Extension.